Mittlere Schwingungsamplituden der Hexachloro- und Hexabromo-Anionen einiger Lanthanide - Baran, Enrique José (1979)
Mean amplitudes of vibration for various octahedral complex compounds of the typeLnCl63− andLnBr63− (withLn=Nd, Eu, Gd, Dy, Er, and Yb) have been calculated, at different temperatures, using known spectroscopic data. The results are briefly discussed and it is found that theLn−Cl andLn−Br amplitude values are highly characteristic.